Models of Wedding Ceremonies in Mass Media - Karapetyan, Anrieta; Sarmakyan, Milena (Journal of Sociology: Bulletin of Yerevan University, 2022)
Mass media creates the audience’s agenda, determines what we should look for. It seeks to change the audience’s behavior, thinking and values, promotes preferred behaviors and perceptions. In the media age, the individual, also, tends to bring the agenda of his/her life in line with the proposed topics, one of which is the wedding ceremony. The procedure of its organization and implementation is presented with different approaches and elements in different countries which is reflected in the movies. Were observed movies containing wedding scenes and wedding photos on social media to understand their impact. The article also summarizes the influence of the mass media, particularly films and photos, on the organization of own wedding ceremony by the Armenian youth, their preferences, which became clear through surveys conducted on the virtual platforms.